2001
DOI: 10.2746/042516401776249543
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of local analgesic solution in the navicular bursa of horses with lameness caused by solar toe or solar heel pain

Abstract: Summary We hypothesised that analgesia of the navicular bursa is not selective for the navicular apparatus; and that solar pain in some horses can be temporarily abolished or attenuated by analgesia of the navicular bursa. To test this hypothesis, we caused lameness in horses by inducing pain in the dorsal margin or the angles of the sole and then evaluated the ability of a local analgesic solution administered into the navicular bursa to attenuate lameness. The response of horses with solar pain in the dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 7 publications
0
29
0
1
Order By: Relevance
“…Moreover, contrary to expectations, analgesia was most effective in the toe region of the sole and least effective in the palmar angles of the sole (Schumacher et al . ). A separate study showed that the volume of local anaesthetic solution injected into the DIP joint could influence the portions of the sole that are desensitised (Schumacher et al .…”
Section: Intra‐articular and Intrathecal Blocks Within The Digitmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, contrary to expectations, analgesia was most effective in the toe region of the sole and least effective in the palmar angles of the sole (Schumacher et al . ). A separate study showed that the volume of local anaesthetic solution injected into the DIP joint could influence the portions of the sole that are desensitised (Schumacher et al .…”
Section: Intra‐articular and Intrathecal Blocks Within The Digitmentioning
confidence: 97%
“…To confound things further, experimentally‐induced solar pain was improved by injection of local anaesthetic solution into either the DIP joint or the navicular bursa (Schumacher et al . ; Sardari et al . ).…”
Section: Intra‐articular and Intrathecal Blocks Within The Digitmentioning
confidence: 99%
“…Others fail to provide any data or mention of assessment following removal of lameness induction techniques (Merkens and Schamhardt, 1988b). In contrast to screw placement near the quarters of the hoof, the persistence of lameness has been recognized more frequently when induced with the screws placed toward the toes, such that lameness remained for at least 24 h (Keegan et al, 2000;Schumacher et al, 2000Schumacher et al, , 2001aSchumacher et al, , 2001b.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, the frog-pressure method, when used on trotting horses, has been shown to produce an inconsistent lameness pattern over time (Keegan et al, 2000;Kelmer et al, 2005). In addition, residual lameness has been reported with the solar pressure technique, with most being in studies where the nuts and screws are placed closer to the toe than the quarter (Deuel et al, 1995;Schumacher et al, 2000Schumacher et al, , 2001aSchumacher et al, , 2001b. The type of screw used may also affect induction of lameness; for example, researchers found greater residual lameness when using flat-tipped screws when compared to pointed screws and it has been speculated that additional pressure and repeated placement may lead to solar bruising (Schumacher et al, 2000(Schumacher et al, , 2001a.…”
Section: Introductionmentioning
confidence: 97%
“…Von Dyson et al (2005) Gelenke sehr kritisch bewertet werden (Dyson 1998, Dyson und Marks 2003 (Schumacher et al 2001). Nach Einwirkungszeit des Lokalanästhetikums von 20 min und länger kann eine Anästhesie der Bursa podotrochlearis auch schmerzhafte Prozesse im Hufgelenk betäuben (Schumacher et al 2003).…”
unclassified